1994
DOI: 10.1055/s-0038-1648966
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Haemophilia in Greece: An Overview

Abstract: SummaryDemographic data of the Greek haemophilia A and B population for the period 1972-1993 were analyzed. Prevalence at birth including known not-registered patients was calculated at 23.1 per 100,000 male births. However, the observed prevalence in 1993 was only 61% of the expected. Since 1975 the proportion of mild cases had significantly increased. Adjusted by age, severity and HIV status reproductive fitness of haemophiliacs was 0.62. Overall mortality was 2.6 times higher than in the general population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 19 publications
6
68
0
1
Order By: Relevance
“…There was a clear reduction in the number of deaths from ischemic heart disease compared with the number expected from general population rates, as has previously been observed in studies of mortality in people with hemophilia in the Netherlands 7 (1 death observed, 5 expected) and Greece 23 (1 death observed, 4 expected). A study of hospital discharge rates in hemophilia in the United For personal use only.…”
Section: Mortality From Cardiovascular Diseasesupporting
confidence: 72%
“…There was a clear reduction in the number of deaths from ischemic heart disease compared with the number expected from general population rates, as has previously been observed in studies of mortality in people with hemophilia in the Netherlands 7 (1 death observed, 5 expected) and Greece 23 (1 death observed, 4 expected). A study of hospital discharge rates in hemophilia in the United For personal use only.…”
Section: Mortality From Cardiovascular Diseasesupporting
confidence: 72%
“…In a larger US study using data from the six-state Hemophilia Surveillance System Project [5], Kulkarni et al [7] demonstrated that the known CVD risk factors (hypertension, diabetes mellitus and hyperlipidemia) were independently associated with IHD in the hemophilia population, similar to the general population. In a prospective study looking at 100 Dutch hemophilia patients, Biere-Rafi et al [16] found that the prevalence of CVD risk factors was similar to the general population, thus supporting the hypothesis that the reduction in cardiovascular mortality that has been reported in hemophilia patients [1][2][3][4]6] is due to their protective hypocoagulability state. Walsh et al [17] also looked at the prevalence of hypertension, diabetes and obesity as part of a study to measure health-related quality of life in the Canadian hemophilia population as compared to the general population.…”
Section: Discussionmentioning
confidence: 82%
“…Although data on the protective effect of hemophilia on cardiovascular diseases (CVDs) are conflicting [1][2][3][4][5][6][7][8], their longevity exposes this group of patients to the same CVD risk factors (hypertension, smoking, diabetes mellitus, hyperlipidemia, obesity) as the general population. There are limited data on the prevalence and management of such risk factors in patients with hemophilia when compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Several European studies [1][2][3] and one U.S. study [4] of cause-specific mortality have found lower rates of death from ischemic heart disease in persons with hemophilia compared to the general population. These findings have been interpreted as providing evidence that the hypocoagulable state offers protection from the thrombotic event that precipitates infarction.…”
Section: Introductionmentioning
confidence: 99%